Petrography of heavitree quartzite, Amadeus basin, central Australia: Implications on depositional environment, provenance and tectonic setting - M. EL Oshebi, Farag; R. Shaltami, Osama; F. Fares, Fares; Errishi, Hwedi; S. El Ekhfifi, Salah (Libyan Journal of Science &Technology, 2022)
Petrographic analysis of the Neoproterozoic Heavitree Quartzite from the Amadeus basin, central Australia was used to interpret the depositional environment, paleoclimate, provenance and tectonic setting. The studied sandstones are mainly classified as quartz arenites. The depositional environment of the Heavitree Quartzite is deltaic based on composition and maturity. The probable paleoclimate for the source area of the Heavitree Quartzite is humid. The detected quartz grains suggest that granitic rocks must be the plausible source of the studied sediments. The studied samples plot in the field of craton interior in the tectonic disc